Analysis of the Effect of Bagasse Addition on Compressive Strength, Porosity, and Permeability of Pervious Concrete as Material for Green Building Program - Harmiyati; Al Ihsyan, Nurman; Syahputri, Devi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Pervious concrete is still not widely used in construction work because it has shortcomings in terms of compressive strength, The researcher tried to increase the percentage of aggregate from wasted materials in the form of bagasse and if the compressive strength of pervious concrete with additional bagasse material has a standard compressive strength of 12 MPa can be applied as parking areas, light-traffic roadways, and sidewalks while maintaining its permeability properties to reduce surface water runoff in construction. Because of these advantages, pervious concrete is often used as a supporting material for Green Building programs in the world. This research method was carried out based on the standardization of SNI 7656-2012 and ACI 522R-10 for testing compressive strength, porosity, and permeability to pervious concrete in the form of cylinders measuring 15 x 30 cm, with variations in the addition of dry bagasse of 0%, 2%, 4%, and 6% by weight of cement. The results of the average compressive strength of pervious concrete at the age of 28 days with a total of 3 samples for variations of 0%, 2%, 4%, and 6% are 12.4 MPa, 14.1 MPa, 16.5 MPa, and 18.9 MPa respectively and are in accordance with the ACI 522R-10 standard. The average porosity results of pervious concrete with a total of 3 samples for variations of 0%, 2%, 4%, and 6% are 23.5%, 20.6%, 19.5%, and 17.4%, respectively. The average permeability results of pervious concrete with a total of 3 samples for 0%, 2%, 4%, and 6% variations are 0.46 cm/sec, 0.33 cm/sec, 0.27 cm/sec, and 0.20 cm/sec, respectively. Therefore, the pervious concrete in this study uses environmentally friendly materials that comply with the first category of water conversion and the second category of material sources and cycles in the Greenship New Building assessment by GBCI.